Optimization of the stabilization of clinical outcomes of orthodontic treatment of tooth-jaw anomalies by pharmacological correction and photophoresis with gel composition «Povichondrohexisole» in adult patients - Мartovlos А.; Hodovanyi, O. (Actual Dentistry, 2018)
Topicality. Treatment of orthodontic anomalies and deformations is a topical problem in modern dentistry. After treatment, normalized form and function of the tooth-jaw system can be maintained under the condition of equilibrium of the bone structures of the alveolar bone at the cellular level, that is, at the formation of the so-called «bone retention». The purpose of this study was to substantiate the benefits of combined effects of laser photophoresis with gel composition and an osteotropic drug based on glycosaminoglycans (GAG) to optimize bone tissue osteogenesis of skeletal bones and bones of the alveolar jaw processes in particular in the retention period of orthodontic treatment. Materials and methods. 110 patients (17–40 years) with orthodontic pathology on the background of generalized periodontitis of initial and I degree of severity participated in the study. The first subgroup of patients (70 people) in the retention period applied an elaborated scheme, which included reteiner, monoblock double-jaw reinforced retention appliance, courses of laser photophoresis with gel composition «Povichondrohexisole» and the appointment of the drug «Teraflex». In the second subgroup (20 people), after active orthodontic treatment, we fixed retainers, prescribed the drug «Teraflex» and locally – performed applications of the gel «Metrodent». In the third subgroup (20 people), retainers were fixed and locally – gel «Metrodent» was applied. The efficiency of the treatment regimen was assessed by X-ray, ultrasonic densitometry and echoosteometry. Results. The procedures of laser photophoresis in combination with the prescription of «Teraflex» in the first subgroup best contributed to the optimization of osteo-reparative processes in the bone tissue of the skeleton and the bone of the alveolar jaw processes, which is confirmed by X-ray, ultrasonic densitometry data (in 6 months, 90.23 % and 12 months later – 94.42 %, which was close to the control intact group – 98.79 % compared with the indicators before treatment – 73.88 %) and echoosteometry (up to the time of treatment ultrasound was 17.98±0.12 μs, and after 6 and 12 months – 14.16±0.24 μs and 15.08±0.18 μs in comparison with the control group – 12.98±0.11 μs). Conclusion. The proposed method for optimizing the stabilization of clinical outcomes of orthodontic treatment of tooth-maxillary anomalies by pharmacological correction of the retention period by the osteotropic drug «Teraflex» in combination with laser photophoresis with gel composition «Povichondrohexisole» based on GAG in young and adult patients has been shown to be most effective. Key words: tooth-jaw anomalies, pharmacological correction, osteotropic preparations, laser photophoresis, glycosaminoglycans, bone retention.